2015
DOI: 10.1007/s10811-015-0758-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of biogas upgrading coupled with nutrient removal from anaerobic effluents using microalgae-based processes

Abstract: The present research was conducted in order to simultaneously optimize biogas upgrading and carbon and nutrient removal from centrates in a 180 L high rate algal pond interconnected to an external CO 2 absorption unit. Different biogas and centrate supply strategies were assessed in order to increase biomass lipid content. Results showed 99% CO 2 removal efficiencies from simulated biogas at liquid recirculation rates in the absorption column of 9.9 m 3 m -2 h -1 , concomitant with nitrogen and phosphorus remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 37 publications
2
13
0
2
Order By: Relevance
“…The presence of this microalga was not detected during stage 2B, when the filamentous cyanobacterium Pseudanabaena minima accounted for 53% of the total number of photosynthetic microorganisms. The high microalgae diversity found in our research was in agreement with that reported in outdoors and indoors pilot HRAPs treating diluted piggery and centrate wastewater [10,38].…”
Section: Microalgae and Bacteria Population Structuresupporting
confidence: 92%
See 4 more Smart Citations
“…The presence of this microalga was not detected during stage 2B, when the filamentous cyanobacterium Pseudanabaena minima accounted for 53% of the total number of photosynthetic microorganisms. The high microalgae diversity found in our research was in agreement with that reported in outdoors and indoors pilot HRAPs treating diluted piggery and centrate wastewater [10,38].…”
Section: Microalgae and Bacteria Population Structuresupporting
confidence: 92%
“…The higher O 2 requirements for complete organic matter oxidation during RV feeding into the AC (stage 3) resulted in biomethane O 2 concentrations in compliance with the requirements of most international legislations for injection of the upgraded biogas in natural gas networks (0.2-1%) [5]. This biomethane O 2 concentration was significantly lower than that recorded by Posadas et al [10], which ranged from 2.0 ± 1.0% to 20.7 ± 0.1%, and by Serejo et al [12], which averaged 2 ± 1%. Likewise, the O 2 concentrations recorded here were significantly lower than those achieved by Mann et al [30] in a 1 L enclosed tubular photobioreactor supporting CO 2 and H 2 S-REs of 97% and 100%, respectively, with biomethane O 2 concentrations ranging from 18-23%.…”
Section: Co 2 and H 2 S Removal And Oxygen Concentration In The Biomementioning
confidence: 86%
See 3 more Smart Citations